2011
DOI: 10.1016/j.ejvs.2011.06.028
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Follow-up of Vascular Reconstructions after Supracondylar Humerus Fracture with Vascular Lesion in Childhood

Abstract: Our data emphasise that surgical reconstruction is effective in terms of blood supply and growth. In cases with interposition of greater saphenous vein or venous patch plasty, we found a high risk for development of enlargements. We suggest that these patients be followed periodically, with ultrasound studies, to detect aneurysms and/or thrombotic changes as early as possible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…Konstantiniuk et al showed in a 14-year follow-up, that surgical reconstruction of the brachial artery is an effective therapy in regard of blood supply and growth. Still, in 7 of 10 patients they found an ectatic lesion of the saphenous vein graft [8] .…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Konstantiniuk et al showed in a 14-year follow-up, that surgical reconstruction of the brachial artery is an effective therapy in regard of blood supply and growth. Still, in 7 of 10 patients they found an ectatic lesion of the saphenous vein graft [8] .…”
Section: Discussionmentioning
confidence: 92%
“…Vascular compromise can be caused by arterial rupture, kinking, compression, spasm or intimal lesion and incidence increases depending on the degree of dislocation [7] . Growth-retardation can be result of conservative therapy of vascular trauma [8] . Even after reduction of the fracture, in up to 47% of the patients with initially vascular compromise, the hand remains pulseless but perfused due to entrapment of the brachial artery within the fracture side.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the outcomes of conservative management, many surgeons-especially vascular or microsurgical surgeons-tend to recommend surgical exploration and vascular reconstruction after CRPP for a PPH, with good results reported. 9,13,14,30 Immediate surgical exploration before fracture reduction has even been recommended, 14 although disadvantages of the procedure have been reported to include a long scar and the occurrence of re-occlusion and stenosis of the brachial artery. 21,28 Surgical exploration is recommended for three main reasons: the rst is that ligation of an injured brachial artery is considered to be associated with a high amputation rate based on war-time reports.…”
Section: Discussionmentioning
confidence: 99%
“…Others recommend aggressive surgical treatment and reconstruction of damaged vessels [14, 32, 35], because reliance on collateral flow in the forearm may leave the hand viable and, however, puts the child at risk for long-term sequelae such as contractures and limb length discrepancy [11, 14]. In some studies, radical treatments with interposition of the greater saphenous vein or the basilic vein for reconstruction of the brachial artery obtained very good and promising results [14, 36]. In our opinion, each case should be considered individually.…”
Section: Discussionmentioning
confidence: 99%